Do functional and phylogenetic nestedness follow the same mechanisms as taxonomic nestedness? Evidence from amphibians in the largest archipelago of China. Issue 12 (31st October 2022) - Chen, Chuanwu; Zhan, Chengxiu; Wang, Yanping
Abstract: Nested subset pattern (nestedness) has been raised to explain the distribution of species on islands and habitat fragments for over 60 years. However, previous studies on nestedness focused on species richness and composition and overlooked the role of species traits and phylogeny in generating and explaining nestedness. To address this gap, we sampled amphibians on 37 land‐bridge islands in the largest archipelago of China, the Zhoushan Archipelago, to explore nestedness as well as the underlying causal processes through three facets of diversity, that is, taxonomic, functional and phylogenetic diversity. The taxonomic nestedness was measured through organizing the species incidence matrix to achieve a maximum value, while the functional and phylogenetic nestedness were quantified by incorporating the similarity of species in terms of their ecological traits and phylogeny. We also obtained six island characteristics and seven species traits as predictors of nestedness. Amphibian metacommunities were significantly nested in these three facets of diversity. When relating different predictors to nestedness, island area, habitat diversity and species traits were highly correlated with taxonomic nestedness. Moreover, island area and habitat diversity significantly influenced functional and phylogenetic nestedness. Therefore, the results support the selective extinction and habitat nestedness hypotheses. Interestingly, although we did not observe significant influences of island isolation on taxonomic nestedness, functional and phylogenetic diversities were significantly higher than expected when matrices were ordered by increasing distance to mainland. The result suggests that there are more functionally and phylogenetically diverse species on less‐isolated islands, reflecting a selective colonization process overlooked by the traditional analysis of taxonomic nestedness. Although the three facets of nestedness and underlying processes were largely congruent, we detected the distance‐related functional and phylogenetic nestedness for amphibian assemblages. Therefore, we highlight that a framework that simultaneously considers taxonomic, functional and phylogenetic nestedness can contribute to a complementary understanding of nestedness processes. In addition, it also improves our ability to conserve insular biodiversity from different perspectives. Abstract : Taxonomic nestedness of amphibians was related to island area, habitat diversity and species traits, but not island isolation. Instead, the functional and phylogenetic nestedness analyses showed that isolation (distance to nearest mainland) was an additional nestedness driver, reflecting the distance‐driven selective colonization process on the assembly of amphibians.